Climatic control of riverine and seawater uranium-isotope ratios. - Robinson, L; Henderson, G; Hall, L; Matthews, I (2004)
The large variation in the ratio of uranium-234 to uranium-238 (234U/238U) in rivers is not well understood, but may provide information about past weathering and rainfall and is important because it controls seawater (234U/238U). Here, we demonstrate the importance of physical weathering and rainfall for (234U/238U), using rivers from South Island, New Zealand. These data allow interpretation of an existing speleothem (234U/238U) record and suggest that New Zealand glacier advance 13,000 years ago was influenced by increased rainfall rather than by Younger Dryas-like cooling. A model of seawater (234U/238U) during glacial cycles indicates that rejection of corals based on modern (234U/238U) +/- <0.01 is not merited and may reject the highest quality ages.